Regulation of Antiviral Immune Response by N6-Methyladenosine of mRNA - Zhao, Baoxin; Wang, Weijie; Zhao, Yan; Qiao, Hongxiu; Gao, Zhiyun; Chuai, Xia (Frontiers in Microbiology, 2021)
The host innate and adaptive immune responses play a key role in clearing the infected viruses. However, viruses also evolve a series of mechanisms to weaken host immune responses and evade immune defense. Some recent studies have shown that m6A, the most prevalent mRNA modification, regulate multiple steps of RNA metabolism including mRNA splicing, localization, stabilization and translation, and affect many biological phenomena including viral infection. In the process of virus-host interaction, the m6A modification that present on the virus RNA impede the capture by the pattern recognition receptors (PRR). And the m6A modification appearing on the host's immune-related molecules regulate interferon response, immune cell differentiation, inflammatory cytokines production and other immune responses induced by viral infection. This review summarizes the research advances about the regulatory role of m6A modification in the innate and adaptive immune responses against viral infections.